2018
DOI: 10.1108/ilt-03-2017-0066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recess depth on lubrication performance of annular recess hydrostatic thrust bearing by constant rate flow

Abstract: Purpose The purpose of this paper is to describe a simulation and experimental research concerning the effect of recess depth on the lubrication performance of a hydrostatic thrust bearing by constant rate flow. Design/methodology/approach The computational fluid dynamics and finite volume method have been used to compute the lubrication characteristics of an annular recess hydrostatic thrust bearing with different recess depths. The performances are oil recess pressure, oil recess temperature and oil film v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…h is the oil film thickness, but in oil chamber filed, h = h pad + h oil . The X is the tangential direction of the circumference and the Z is the radial direction of thrust bearing which is the main capacity direction [27]. In Figure 2b A-A face, dynamic eddy current will be formed in this area with the change of pressure gradient under the condition of high pressure and high speed.…”
Section: Modelling and Analysis Of The Hydrostatic Bearing Spindlementioning
confidence: 99%
“…h is the oil film thickness, but in oil chamber filed, h = h pad + h oil . The X is the tangential direction of the circumference and the Z is the radial direction of thrust bearing which is the main capacity direction [27]. In Figure 2b A-A face, dynamic eddy current will be formed in this area with the change of pressure gradient under the condition of high pressure and high speed.…”
Section: Modelling and Analysis Of The Hydrostatic Bearing Spindlementioning
confidence: 99%
“…The continuity equation of compressible fluid is given by Shao et al (2017): The equation of gas state …”
Section: Governing Equationmentioning
confidence: 99%
“…The pocket geometry and compensating elements play an important role in achieving adequate stiffness in the hydrostatic bearing. Numerical and experimental studies were reported with capillary and orifice (Rowe, 2013), membrane (Gohara et al , 2014), porous land surface (Hanawa et al , 2017), constant-flow valve (CFV) (Shao et al , 2018), displacement compensator (Vladimir et al , 2021), etc., which have been used as compensating elements in the hydrostatic bearings. Hanawa et al (2017), performed numerical and experimental studies to investigate the effect of providing a porous surface on static stiffness of a capillary-compensated thrust bearing.…”
Section: Introductionmentioning
confidence: 99%